Hyperspectral Remote Sensing And Spectral Signature Applications - Rajendran, S. (New India Publishing Agency (NIPA), 2021)
The title of "hyperspectral remote sensing and spectral signature applications" is use to reflect its focus on spectral techniques, i.e. non-literal techniques that are especially designed and developed for hyperspectral imagery rather than multispectral imagery